The authority of the Old Testament - Bright, John, 1908 September 25-1995; Bright John; The Authority Of The Old Testament (Nashville : Abingdon Press, 1967)
What is the nature of the authority of Scripture, and in what sense does the Old Testament share that authority? What place does the Old Testament legitimately occupy in the Christian's Bible and in the church's proclamation? What principles ought to guide one in interpreting it to the congregation? These are the questions with which this book will attempt to deal, with what success the reader must judge. - Foreword
The authority of the Old Testament: the nature of the problem -- The problem of the Old Testament: the "classical" solutions -- Biblical theology and the authority of the Old Testament -- The Old Testament in the Christian pulpit: general hermeneutical considerations -- Preaching from the Old Testament: the principles illustrated
Includes bibliographical references (pages 253-261)
Keywords: Bright John; Bible. -- Hermeneutics; Bible. -- Homiletical use